Kinetics study of pb (ii) adsorption on xanthated leucaena leucocephala leaf powder / Mardhiah Ismail and Liyana Ainun Yamin - Ismail, Mardhiah; Yamin, Liyana Ainun (Universiti Teknologi MARA Cawangan Pahang, 2021)
Leucaena leucocephala (LL) is abundant and has the potential to be a cheap and readily available biosorbent. This species is among the fast-growing trees, which is widely used in Malaysia including in the furniture industry for its wood. In this study, LL leaf powder was treated with xanthate and evaluated for its act in the removal of low concentration Pb (II) ion from aqueous solution. The functional groups of xanthates-treated L. leucocephala leaf powder (XLL) was investigated using the ATR-Fourier Transform Infrared (ATR-FTIR) analysis. The study also covered the influence of several parameters on the adsorption of Pb (II) onto XLL, such as pH, adsorbent dosage, and kinetics. The optimum pH range for Pb (II) adsorption was at pH 4. Two kinetic models; pseudo-first-order model and pseudo-second-order model, were used to analyze the Pb (II) adsorption process, and the results showed that the pseudo-second-order model close-fitting well with a correlation coefficient, R2, of 0.99. The maximum adsorption capacity of Pb (II) was 76.34 mg g-1. This study hopes to increase the value of this fast-growing tree species.